The practice of ringing the bell - Mumbai Archive Project Team (Jio Institute, 2024)
A father teaches his child to ring a temple bell. Ringing the bell is considered a way to invite the deity and announce one's presence. The sound of the bell is believed to dispel negative energies and purify the environment.